Outcomes of patients with chronic phase chronic myeloid leukemia (CML-CP) after discontinuation of frontline ponatinib therapy. Issue 13 (10th November 2019) - Boddu, Prajwal; Jain, Preetesh; Borthakur, Gautam; Verstovsek, Srdan; Garcia-Manero, Guillermo; Daver, Naval; Kadia, Tapan; Ravandi, Farhad; Jabbour, Elias; Cortes, Jorge; Kantarjian, Hagop
Abstract: Considering the risk of arterio-thrombotic adverse events (AEs), ponatinib trials in previously untreated chronic myeloid leukemia chronic phase (CML-CP) were terminated. We conducted a retrospective CML-CP outcome study of patients who discontinued frontline-ponatinib. Among 51 patients who received frontline ponatinib, 38 discontinued because of FDA request and 13 due to AEs. At ponatinib discontinuation, all patients remained in CP with deepest response being CCyR, n  = 7; PCyR, n  = 4; MMR, n  = 14; MR4.5, n  = 26. Of the four patients in PCyR at ponatinib discontinuation, two improved response to CCyR on subsequent TKI. Of seven patients, in CCyR at discontinuation, five improved response to MMR or deeper, one was inevaluable, and another lost response due to treatment noncompliance. With a median follow-up of 39 months, 3-year EFS and OS were 92% and 96%, respectively, indicating favorable long-term outcomes. The cardiac/vascular system AEs with subsequent TKI occurred in patients with prior similar events on ponatinib. AEs occurred up to 9 months post-ponatinib.